Aerodynamic response of high-speed trains under crosswind in a bridge-tunnel section with or without a wind barrier. Issue 210 (March 2021) - Deng, E.; Yang, Weichao; He, Xuhui; Zhu, Zhihui; Wang, Hanfeng; Wang, Youwu; Wang, Ang; Zhou, Lei
Abstract: High-speed trains experience a sharp transition to a strong crosswind environment when running in a bridge–tunnel section due to the perennial prevailing crosswind in the canyon, and this sudden transition seriously affects train safety. In this study, a 3D computational fluid dynamics numerical model of the train–tunnel–bridge–wind barrier is established based on the delayed detached eddy simulation turbulence model and porous media theory. A dynamic analysis model of wind–train–bridge coupling is adopted. The effects of wind barrier with a height of 3 ​m and porosity of 30% on the aerodynamic coefficient, flow field structure and running safety of high-speed trains under crosswind in the bridge–tunnel section are studied. Results indicate that the sharp change effect of the aerodynamic coefficient is significantly weakened by more than 50% by the wind barrier. The aerodynamic fluctuation amplitudes in the bridge–tunnel section are 1.25–5.5 times higher than those in the bridge section. The difference in pressure distribution in the longitudinal direction is significantly reduced because of the obstruction and diversion of the wind barrier and the space limitation on the windward side. Accordingly, the change in amplitude of the aerodynamic coefficients in the bridge–tunnel section is reduced, and so is the safety of train operation. The bridge–tunnel section is the weak link of safety control. Using a wind barrier with the same parameters for the bridge and bridge–tunnel sections is unreasonable, that is, the parameters should be separately designed. Highlights: The wind-vehicle-bridge coupled analysis system based on DDES method is proposed. A 3D CFD numerical model of train-tunnel-bridge-porous media-air is established. The windproof performance of the wind barrier at bridge-tunnel section is revealed. A preliminary idea for the optimal design of wind barriers at the bridge-tunnel section is proposed.